Fundamentals of water treatment unit processes: physical, chemical and biological - Hendricks, David W. (CRC Press, 2011)
"Carefully designed to balance coverage of theoretical and practical principles, this textbook delineates the principles that support practice, using the unit processes approach as the organizing concept. Since technologies change but principles remain constant, the author identifies strands of theory rather than discusses the latest technologies, giving students a clear understanding of basic principles. With chapter glossaries, sidebars, illustrative examples, spreadsheet tables, problems, and a solutions manual, this book offers a complete presentation of the full scope of biological treatment. Additional supporting material is available for download on the web"--